Mass Determination of Entire Amyloid Fibrils by Using Mass Spectrometry. (23rd December 2015) - Doussineau, Tristan; Mathevon, Carole; Altamura, Lucie; Vendrely, Charlotte; Dugourd, Philippe; Forge, Vincent; Antoine, Rodolphe
Abstract: Amyloid fibrils are self‐assembled protein structures with important roles in biology (either pathogenic or physiological), and are attracting increasing interest in nanotechnology. However, because of their high aspect ratio and the presence of some polymorphism, that is, the possibility to adopt various structures, their characterization is challenging and basic information such as their mass is unknown. Here we show that charge‐detection mass spectrometry, recently developed for large self‐assembled systems such as viruses, provides such information in a straightforward manner.